Characterisation of gas-liquid two-phase flow in minichannels with co-flowing fluid injection inside the channel, part II: gas bubble and liquid slug lengths, film thickness, and void fraction within Taylor flow. (January 2017) - Haase, S.
Highlights: Downward gas–liquid flow was studied experimentally at a pressure of 1 MPa. Capillary injectors of different diameters were used as gas-liquid feeding system. Bubble formation was analysed in detail for various homogeneous Taylor flows. Novel correlations to predict gas bubble and liquids slug lengths are provided. The equations are based on significant dimensionless numbers. Abstract: Current research proofs the potential of apparatuses containing minichannel flow structures to intensify gas-liquid-solid contacting processes. The excellent heat and mass transfer in these devices as well as a sharp RTD mainly result from the Taylor flow regime. A proper design of corresponding contactors requires precise information on the provided interfacial areas. However, the characterisation of gas-liquid Taylor flow with industrially relevant fluids at elevated pressure and created by capillary injection devices gained little attention so far. This work analyses adiabatic gas-liquid Taylor flow in a square minichannel of 1.0 mm hydraulic diameter using water, water-glycerol, or water-ethanol mixtures as liquid phase and hydrogen or nitrogen as gas phase to cover a broad range of material parameters. In the mixing zone located within the flow channel, gas was injected into the co-flowing liquid by so-called capillary injectors with variable inner diameter (0.184, 0.317, 0.490 mm). Two different bubble forming mechanisms were identified leading to a complex interaction between physical properties of the fluids, geometrical parameters and the observed gas bubble and liquid slug lengths. According to the Pi-theorem, these lengths were affected by 6 dimensionless groups, namely (uG, s / uL, s ), Re L, WeL, (dIn, CI / dh ), (dOu, CI / dh ), and Θ * . Based on more than 370 experimental data, novel correlations to predict gas bubble and liquid slug lengths were developed. Graphical abstract: